Anxious Attachment Style Predicts Pathological Internet Use in Nursing Students: The Mediating Role of Alexithymia. - Adıgüzel, Vesile; Su Topbas, Zehra; Sampaio, Francisco (Perspectives in Psychiatric Care, 2025)
Aim: The study was aimed at determining the mediating role of alexithymia in the relationship between anxious attachment style and internet addiction in nursing students. Method: The current cross‐sectional study was conducted with nursing students studying in a province located in western Türkiye. The study data were collected from 266 students using the face‐to‐face interview technique with the self‐report scales between February 2024 and June 2024. The descriptive statistics and correlation analyses of the current study were performed using the SPSS (Statistical Package for the Social Sciences) 25.0 program, and the mediating role analysis was conducted using the PROCESS Macro model 4 for SPSS. The data obtained were analyzed with descriptive statistics, correlation analysis, and mediating role analysis. Results: The mean age of the participants was 21.18 (Min: 18, Max: 28). Of them, 165 (62%) were men, 101 (38%) were women, and only 3 (1%) were married. The time they spent for daily internet use varied between 1 and 5 h. Anxious attachment style predicts pathological internet use and alexithymia. At the same time, alexithymia predicts pathological internet use. Mediator role analyses indicate that alexithymia is a mediator in the relationship between anxious attachment and internet addiction (p < 0.05). Conclusion: Nursing students, who will perform nursing, which has a crucial position in health services, should be provided with trainings on attachment styles, correct internet use, recognizing, and expressing emotions, and students at risk should be recognized and provided with professional psychosocial support if necessary. Testing the study hypotheses on nursing students in different regions would be beneficial for generalizing the findings. Considering the role of different attachment styles, it would be useful to investigate other variables that may mediate the relationship between attachment styles and pathological internet use.